2009
DOI: 10.1002/chir.20693
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazinoanthrylboronic acids as exciton‐coupled circular dichroism (ECCD) probes for multivalent catechols, particularly epigallocatechin gallate

Abstract: We report the use of exciton-coupled circular dichroism (ECCD) spectroscopy in multianalyte sensing systems in complex matrices. To prepare ECCD sensors, anionic anthrylhydazides are reacted with formylphenylboronic acids to give hydrazinoanthrylboronic acids that in turn are reacted with multivalent catechols in aqueous solution. The ECCD signal between the anthracene chromophores in the resulting boronate ester products depends strongly on the structure of the boronic acid sensor and the polyphenol analyte. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…This finding suggested that in the confined space of multicomponent surface architectures S1H2B6, boronic-ester formation occurs always with both catechols in PV B5, thus stabilizing the colorful but intrinsically disfavored tritylium cation in PV B5 (Fig. 23 Constraints by the confined space 14a or, less likely, 14d,e kinetic traps from strong binding could account for this relatively low η MAX . In solution, boronic-ester formation always occurred through the monoester *H2B5 (Fig.…”
Section: Pyrocatechol Violetmentioning
confidence: 95%
“…This finding suggested that in the confined space of multicomponent surface architectures S1H2B6, boronic-ester formation occurs always with both catechols in PV B5, thus stabilizing the colorful but intrinsically disfavored tritylium cation in PV B5 (Fig. 23 Constraints by the confined space 14a or, less likely, 14d,e kinetic traps from strong binding could account for this relatively low η MAX . In solution, boronic-ester formation always occurred through the monoester *H2B5 (Fig.…”
Section: Pyrocatechol Violetmentioning
confidence: 95%
“…High activity and incomplete co-TSA were both consistent with the large size and the multivalencyo fB5 (Figure 1). [7] Polyphenon 60 (B6), ac ommercially available green-tea extract, inhibited TSA of B1 to S1H3 with an IC 50 = 5.1 mg mL À1 (Figure 3d;T able 1, entry 11). This intermediate activity was very meaningful considering that the weaker catechin (B4)a nd the stronger epigallocatechin gallate (B5)a re the main polyphenols present in green tea.…”
Section: Entries 3-8)mentioning
confidence: 99%
“…[7] Polyphenon 60 (B6), ac ommercially available green-tea extract, inhibited TSA of B1 to S1H3 with an IC 50 = 5.1 mg mL À1 (Figure 3d;T able 1, entry 11). [7] Taken together,t hese results demonstrate the existence and functional relevance of multicomponent architectures that operate with three different dynamic covalent bonds, namely disulfides,h ydrazones,a nd boronic esters.P ossible applications are diverse;directionality and compatibility with optoelectronic signal generation, transduction and detection, interfacing, and device fabrication appear particularly advantageous. Compatibility of dose-response curves for polyphenon 60 with enzymatic signal generation for polyphenol sensing applications has been demonstrated previously in adifferent context.…”
Section: Entries 3-8)mentioning
confidence: 99%
See 2 more Smart Citations